2006
DOI: 10.1002/hed.20365
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteases in head and neck cancer

Abstract: Matrix metalloproteases (MMPs) are a collection of enzymes capable of cleaving extracellular matrix components, growth factors, and cell-surface receptors. MMPs modulate most aspects of tumorigenesis and are highly expressed in cancer compared with normal tissues. Preclinical studies have demonstrated that head and neck squamous cell carcinomas (HNSCCs) express high levels of MMPs in vivo and that inhibition of these enzymes in vitro and in mouse models decreases invasion and metastasis. However, the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
146
1
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(173 citation statements)
references
References 83 publications
(86 reference statements)
9
146
1
15
Order By: Relevance
“…24,25 Preclinical trials have shown that squamous cell carcinomas express high levels of MMPs in vivo and that the inhibition of these enzymes in vitro and in animal models reduces the invasion potential and metastatic capacity of the tumor. 2 Regarding the expression of MMP-9 in odontogenic cysts and tumors, in the present study epithelial and mesenchymal cells of the lesions studied diffusely secreted this protein. This finding suggests a role of MMP-9 in tumor growth, because the protein is known to act on the remodeling of ECM and the degradation of bone matrix.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…24,25 Preclinical trials have shown that squamous cell carcinomas express high levels of MMPs in vivo and that the inhibition of these enzymes in vitro and in animal models reduces the invasion potential and metastatic capacity of the tumor. 2 Regarding the expression of MMP-9 in odontogenic cysts and tumors, in the present study epithelial and mesenchymal cells of the lesions studied diffusely secreted this protein. This finding suggests a role of MMP-9 in tumor growth, because the protein is known to act on the remodeling of ECM and the degradation of bone matrix.…”
Section: Discussionmentioning
confidence: 50%
“…In the case of tumors, this situation contributes to the growth and higher aggressiveness of the tumor. 2 The odontogenic keratocyst, recently reclassified as keratocystic odontogenic tumor (KOT), 3 is known for its aggressive nature and high rate of recurrence, especially compared with other odontogenic cysts. 4 Ameloblastoma is a locally aggressive benign epithelial odontogenic tumor with a marked invasion potential that results in multiple recurrences after enucleation and curettage.…”
mentioning
confidence: 99%
“…Preclinical trials have shown that SCCs express high levels of MMPs in vivo and that inhibition of these enzymes in vitro and in animal models is associated with invasiveness and metastasis (14). However, other studies were unable to confirm these results (4,9).…”
Section: Discussionmentioning
confidence: 99%
“…MMP inhibitors may also fail as monotherapy, as they have little cytotoxic effects. Dosing was limited by musculoskeletal side effects, and thus it remains unclear whether other modalities of applying the medication could be beneficial (55).…”
Section: Tissue Invasion and Metastasismentioning
confidence: 99%